Tax Avoidance in Asian Manufacturing Firms: A Cross-Country Analysis of Financial Attributes and Law Enforcement - Listya Eka Maharani; Dian Anita Nuswantara; Yuni Khoirotul Abdiyah; Ruben Jr Nayve; Siti Zabedah Binti Saidin (ccounting Department, Universitas Syiah Kuala, Indonesia, 2026)
This study examines the impact of firm size, leverage, and profitability on tax avoidance across six Asian jurisdictions (IDX, Bursa Malaysia, SET, PSE, SGX, HKEX) from 2020 to 2024. Analyzing 981 manufacturing companies using the Random Effect Model and Moderated Regression Analysis, the results reveal that larger firm size and higher profitability significantly reduce tax avoidance, while leverage and law enforcement enforcement as a moderator show no significant effects. These findings suggest that internal strategic factors and economic incentives supersede external legal pressures, highlighting the limitations of deterrence theory in cross-country corporate taxation.